Tabetri™ (Tabebuia avellanedae Ethanol Extract) Ameliorates Atopic Dermatitis Symptoms in Mice - Jae Gwang Park; Young-Su Yi; Sang Yun Han; Yo Han Hong; Sulgi Yoo; Eunji Kim; Seong-Gu Jeong; Adithan Aravinthan; Kwang Soo Baik; Su Young Choi; Jung-Il Kim; Young-Jin Son; et al. (Mediators of Inflammation)
Tabebuia avellanedae has been traditionally used as an herbal remedy to alleviate various diseases. However, the plant’s pharmacological activity in allergic and inflammatory diseases and its underlying mechanism are not fully understood. Therefore, we investigated the pharmacological activity of Tabetri (T. avellanedae ethanol extract (Ta-EE)) in the pathogenesis of AD. Its underlying mechanism was explored using an AD mouse model and splenocytes isolated from this model. Ta-EE ameliorated the AD symptoms without any toxicity and protected the skin of 2,4-dinitrochlorobenzene- (DNCB-) induced AD mice from damage and epidermal thickness. Ta-EE reduced the secreted levels of allergic and proinflammatory cytokines, including histamine, immunoglobulin E (IgE), interleukin- (IL-) 4, and interferon-gamma (IFN-γ) in the DNCB-induced AD mice. Ta-EE suppressed the mRNA expression of T helper 2-specific cytokines, IL-4 and IL-5, and the proinflammatory cytokine IFN-γ in the atopic dermatitis skin lesions of AD mice. Moreover, Ta-EE suppressed the mRNA expression of IL-4, IL-5, IFN-γ, and another proinflammatory cytokine, IL-12, in the Con A-stimulated splenocytes. It also suppressed IL-12 and IFN-γ in the LPS-stimulated splenocytes. Taken together, these results suggest that Ta-EE protects against the development of AD through the inhibition of mRNA expression of T helper 2-specific cytokines and other proinflammatory cytokines.